OPTIMALISASI PENINGKATAN PERAN LAZIZNU KEPANJEN KABUPATEN MALANG DALAM PEMBIAYAAN PENDIDIKAN - Siti Muawanatul Hasanah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2022)
LAZIZ and its role as a source of funding to assist the educational process. Not only in the field of education, in fact Laziz is an institution that is engaged in the development and empowerment of the people. is one of the zakat institutions that is solemn in empowering the community through productive utilization of zakat funds, infaq, waqf and other philanthropic funds from individuals, institutions, companies and other agencies. Laziz as an institution devoted to community empowerment through zakat funds has an empowerment program in the field of education. one of the educational empowerment programs is realized in the form of scholarship assistance for the poor and orphans. This is where the LAZIZNU Kepanjen Malang district also takes on a role regarding education financing. Keywords: Optimizing the Role of Laziznu, Education Financing.